Securitization and lending standards: evidence from the wholesale loan market - Alper Kara; David Marqués-Ibá\~nez; Steven Ongena (European Central Bank (ECB), 2011)
We investigate the effect of securitization activity on banks' lending standards using evidence from pricing behavior on the syndicated loan market. We find that banks more active at originating asset-backed securities are also more aggressive on their loan pricing practices. This suggests that securitization activity lead to laxer credit standards. Macroeconomic factors also play a large role explaining the impact of securitization activity on bank lending standards: banks more active in the securitization markets loosened more aggressively their lending standards in the run up to the recent financial crisis but also tightened more strongly during the crisis period. As a continuum of this paper we are examining whether individual loans that are eventually securitized are priced more aggressively by using unique European data on individual loans from all major trustees.
Keywords: G21; G28; 330; bank risk taking; financial crisis; securitization; syndicated loans; Verbriefung; Bankrisiko; Kreditgeschäft; Finanzkrise; Europa